Mitigation of environmental effects of frequent flow ramping scenarios in a regulated river - Alfredsen, Knut; Juárez-Goméz, Ana; Refaei Kenawi, Mahmoud Saber; Graf, Magnus Simon; Saha, Sanjoy Kumar (Frontiers in Environmental Science, 2022)
In the transition to a society based on renewable energy, flexibility is important in balancing energy supply as more intermittent sources like wind and solar are included in the energy mix. Storage-based hydropower systems are a renewable energy source that provides the needed flexibility since a hydropower plant can be started and stopped in minutes and the reservoirs provide stored energy that can be utilized when the demand arises. Thereby, the hydropower plants can balance the variability in other energy sources e.g., when there is no wind or when solar input is low. This need for increased flexibility has led to research into new hydro power turbines to provide larger ramping rates, more frequent start and stops and other system services. A possible drawback of ramping operation of hydropower plants (often termed “hydropeaking”) is adverse effects on the environment in the receiving water bodies downstream of the power plant outlet, particularly when the hydropower outlet is in rivers. Rapid changes in flow can lead to stranding of fish and other biota during the shutdown of the turbine and flushing of biota during the start of the turbine. These effects can also be caused by other sudden episodes of water withdrawal, as in accidental turbine shutdowns. The main objective of this paper is to describe a method of designing the necessary volume of water needed to mitigate a fast-ramping turbine, and the effect this has in the downstream river reach. We used a 2D hydraulic model to find the areas affected by hydropeaking operation and further to define areas with a faster ramping rate than 13 cm/h which is used as a limit in the Norwegian guidelines. Based on this we developed a ramping regime that would prevent fast dewatering of critical areas and provided this as a basis for mitigating effects of fast dewatering in the downstream river (River Nidelva in Norway used as a test case). Further, the effect of increasing the frequency of start – stop cycles was studied and the proposed mitigation was evaluated for the new operational regime.